Usefulness of the INNOVANCE® PFA P2Y test cartridge for the detection of patients with congenital defects of the platelet P2Y12 receptor for adenosine diphosphate - Scavone, Mariangela; Germanovich, Ksenia; Femia, Eti A.; Cattaneo, Marco (Thrombosis research, 2014)
The platelet function analyzer (PFA)-100® is used in clinical practice to screen patients with bleeding diathesis and suspected defects of primary hemostasis. A new cartridge, INNOVANCE® PFA P2Y, has been specifically developed to monitor patients’ response to drugs inhibiting the platelet P2Y12 receptor for ADP. In this study, we compared the ability of INNOVANCE® PFA P2Y to detect congenital defects of the platelet P2Y12 receptor to that of standard cartridge formulations currently in clinical use. We studied two patients with severe P2Y12 deficiency, one patient with heterozygous P2Y12 deficiency and one with dysfunctional P2Y12 receptor. Closure times were measured using 3 cartridges: collagen/ADP, collagen/epinephrine, and INNOVANCE® PFA P2Y. The results obtained in the four patients with P2Y12 defects were compared to those obtained for 20 healthy controls. In 2 patients with severe P2Y12 deficiency, closure times of INNOVANCE® PFA P2Y and collagen/ADP cartridges were >300s, while those of collagen/epinephrine cartridge were variable (186s and >300s). In the patient with dysfunctional P2Y12, closure time of INNOVANCE® PFA P2Y was >300s, while closure times of collagen/ADP and collagen/epinephrine were normal. Closure times of all cartridges were normal in the patient with heterozygous P2Y12 deficiency. Our study provides the first evidence that INNOVANCE® PFA P2Y cartridge is sensitive to congenital severe and moderate defects of the platelet P2Y12 receptors.